Newly isolated sporopollenin microcages from Cedrus libani and Pinus nigra as carrier for Oxaliplatin; xCELLigence RTCA-based release assay - Mujtaba, Muhammad; Yilmaz, Bahar Akyuz; Cansaran-Duman, Demet; Akyuz, Lalehan; Yangın, Sevcan; Kaya, Murat; Çeter, Talip; Khawar, Khalid Mahmood (Springer Science and Business Media LLC, 2021)
Sporopollenin-mediated control drug delivery has been studied extensively owing to its desirable physicochemical and biological properties. Herein, sporopollenin was successfully extracted from C. libani and P. nigra pollens followed by loading of a commonly known anticancer drug Oxaliplatin. Drug loading and physicochemical features were confirmed by using light microscopy, FT-IR, SEM and TGA. For the first-time, real-time cell analyzer system xCELLigence was employed to record the Oxaliplatin loaded sporopollenin-mediated cell death (CaCo-2 and Vero cells) in real time. Both the release assays confirmed the slow release of oxaliplatin from sporopollenin for around 40–45 h. The expression of MYC and FOXO-3 genes has been significantly increased in CaCo2 cell and decreased non-cancerous Vero cell confirming the fact that sporopollenin-mediated control release of oxaliplatin is promoting apoptosis cell death preventing the spread of negative effects on nearby healthy cells. All the results suggested that C. libani and P. nigra can be suitable candidates for the slow delivery of drugs.
Keywords: Real-time Cell Analyzer; Controlled-drug Release; Sporopollenin; SDG 3 - Good Health and Well-being; xCELLigence; Controlled-drug release; Real-time cell analyzer; 3. Good health